PENGARUH PERENCANAAN PAJAK DAN CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Yuono, Citra Ayuning Sari; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
Every company has objectives to give prosperity to the stakeholders by maximizing the firm value. In order to create optimal prosperity of the stakeholders, the company is required to use their resource efficiently, to operate on optimal productivity level, and to manage the tax expense properly. A company, in its process to achieve their objectives, it might be possible that the manager will act opportunistically by taking personal profit before the interest of the stakeholders has been fulfilled, therefore good governance is required so that the objectives can be realized appropriately, and the management performance can be supervised and monitored so that fraud does not occur in the financial statements of the company.This research is meant to find out the influence of tax planning and corporate governance to the firm value. The analysis technique has been done by using multiple linear regressions, F test, and t test and coefficient determination. Based on the result of this research, it shows that tax planning and audit committee have significant and positive influence to the firm value. Meanwhile, the managerial ownership, institutional ownership, and independent commissioner do not have any influence to the firm value. Based on the result of this research, the investors should observe the tax planning and composition of audit committee of the company as the information in investment decision making, because it describes the prospect of the company in the future.Keywords: tax planning, corporate governance, firm value